PENGARUH PESAN FEAR APPEAL TERHADAP SIKAP MEMATUHI PROTOKOL KESEHATAN: (Pesan fear appeal dalam kampanye pencegahan Covid-19 oleh Pemprov DKI Jakarta) - Kirana Luthfiah Noor Azizah (2021)
In order to accelerate the handling of the corona virus outbreak, the Provincial Government of DKI Jakarta has implemented various policies to reduce the rate of virus transmission and intensify socialization related to the campaign for implementing health protocols as a form of Covid-19 prevention. In August 2020, the Government of DKI Jakarta brought a new theme for the campaign to prevent the spread of Covid-19, namely by using coffins. The purpose of this study was to determine the effect of fear appeal message in the Covid-19 prevention campaign using coffin on the complying attitude of 3M health protocols. The explanative quantitative was used as research method. This research foundation is based on Extended Paralell Process Model (EPPM). The research data is collected using questionnaires that distributed to 100 respondents. The result of the correlation test stated that fear appeal message (X) and the complying attitude of health protocols had a strong relationship level based on 0.724 value. Based on the result of simple linear regression test, variable X had the positive impact on variable Y. Based on the hypothesis test using t test formula, the result is (8.411) > t table value (1.966). So, the conclusion stated that there's impact of the covid-19 prevention campaign message using coffins on the attitude of complying with health protocols.